Observation of ? (3686)? ? (1530)- ? ? (1530)+ and ? (1530)- ? ? + - Çetin, Serkant Ali (American Physical Society, 2019)
Using 448.1×106 ?(3686) events collected with the BESIII detector at BEPCII, we employ a single-baryon tagging technique to make the first observation of ?(3686)??(1530)-??(1530)+ and ?(1530)-??+ decays with a statistical significance of more than 10? and 5.0?, respectively. The branching fractions are measured to be B(?(3686)??(1530)-??(1530)+)=(11.45±0.40±0.59)×10-5 and B(?(3686)??(1530)-??+)=(0.70±0.11±0.04)×10-5. The angular distribution parameter for ?(3686)??(1530)-??(1530)+ is determined to be ?=0.40±0.24±0.06, which agrees with the theoretical predictions within 1?. The first uncertainties are statistical, and the second systematic.